How gratified are Malaysians and will they continue watching movies on youtube? - Abu Bakar, Mohd Syuhaidi; Bolong, Jusang; Bidin, Rosmiza (Academia Industry Networks, 2020)
Movies nowadays can easily be found online via Astro First, Netflix and iFlix, thus, it is not a surprise that movie production is increasingly leaning towards making movies available in digital format, rather than in the traditional analogue print film. Studies also found significant effect provided by YouTube to the downfall of the cinema business, worldwide. Thus, this study intends to identify how gratified are Malaysians in watching movies on YouTube and what are their continuance intention. This study involved citizens of Malaysia that have used YouTube to watch movies (n=400), chosen using purposive sampling. An online survey using Google Forms were used for data collection. A 4-point Likert scale was used for the gratification and continuance intention constructs. Data were analyzed with SPSS using descriptive statistics and regression analysis. Results show a statistically positive significant relationship between gratification provided by YouTube for movie watching experience; with continuance intention to watch movies on YouTube, thus the hypothesis is accepted. Results also show that respondents were satisfied with the performance YouTube for movie watching pleased with the experience of using YouTube for movie watching (among others findings). These findings should further inspire YouTube to explore distribution agreements with local production companies and create better experiences for movie-watching activities on a user-generated content site. Google should strive to develop a better synergetic business strategy in terms of content selection of movies and provide better actual experience for its stakeholders.